Development and Analysis of Synbiotic Food Products using Musa acuminata Peels as a Strategy Towards Sustainable Utilization of Food Wastes - Pal, A. D.; Parveen, S. (Journal of Scientific Research, 2025)
Food waste is a global issue, and improper waste management contributes to environmental and economic issues. This study aims to address this by repurposing nutrient-rich banana peels of Musa acuminata into sustainable synbiotic food. The peels were fermented with Lactobacillus rhamnosus, resulting in pickles with synbiotic effects. The developed pickles showed high organoleptic acceptability (8.67), with sufficient viable probiotics (5.3 x 109) and significant macronutrients, fiber, micronutrients, and phytochemicals. They also displayed free radical scavenging potential (88.09 %) and a desirable titratable acidity (7.68). The pickles were found to retain considerable viable L. rhamnosus after exposure to simulated gastrointestinal microenvironments. Furthermore, these were observed to be low-cost, manifesting a shelf life of 25 days (room temperature) with appreciable retention of sensory properties, acidity, and live probiotics, demonstrating their potential as a sustainable synbiotic food. This study highlights banana peels as a valuable resource in functional food innovation, promoting a zero-waste approach while imparting positive health effects.